Bibliometric Analysis of Green Investment in Electric Vehicles - Loso Judijanto; Helda Yusita (West Science Social and Humanities Studies, 2026)
The present study conducts a bibliometric review of scholarly work related to green investment for electric vehicles (EVs). The main objective of the review is to provide an insight into the knowledge base of green investment in EVs in terms of the intellectual structure, theme evolution, and international collaboration. Bibliographic information collected from the Scopus database is analyzed using bibliometric techniques including co-occurrence, co-authorship, co-citation, and density analysis. Results demonstrate that the knowledge base is predominantly organized in three domains, which are: EV technological advancement (focusing on battery system and charging infrastructure development); green investment mechanisms and policy (such as subsidy programs, ESG integration, and corporate governance); and the transition towards sustainability (covering topics of renewable energy systems, such as hydrogen and solar energy). In terms of citation analysis, foundational studies cover the topic of lithium battery recycling, EV infrastructure development, and EV battery system development, whereas recent papers are concerned with system integration, decarbonization approaches, and multi-energy mobility ecosystem